Zespół przetrenowania w sporcie - mechanizm, objawy, przyczyny = Overtraining in sport - mechanism, symptoms, causes - Bartosz Kochański; Anna Kałużna; Krystian Kałużny; Łukasz Wołowiec; Walery Zukow; Wojciech Hagner (Kazimierz Wielki University, 2015)
Kochański Bartosz, Kałużna Anna, Kałużny Krystian, Wołowiec Łukasz, Zukow Walery, Hagner Wojciech. Zespół przetrenowania w sporcie - mechanizm, objawy, przyczyny = Overtraining in sport - mechanism, symptoms, causes. Journal of Education, Health and Sport. 2015;5(10):51-60. ISSN 2391-8306. DOIhttp://dx.doi.org/10.5281/zenodo.31946 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%2810%29%3A51-60 https://pbn.nauka.gov.pl/works/649284 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011-2014http://journal.rsw.edu.pl/index.php/JHS/issue/archive   Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 02.08.2015. Revised 05.09.2015. Accepted: 29.09.2015.   Zespół przetrenowania w sporcie - mechanizm, objawy, przyczyny Overtraining in sport - mechanism, symptoms, causes   Bartosz Kochański1, Anna Kałużna1, Krystian Kałużny1, Łukasz Wołowiec2, Walery Zukow3, Wojciech Hagner1   1Katedra i Klinika Rehabilitacji, Wydział Nauk o Zdrowiu, Uniwersytet Mikołaja Kopernika w Toruniu; 2II Katedra Kardiologii, Wydział Nauk o Zdrowiu, Uniwersytet Mikołaja Kopernika w Toruniu;3Wydział Kultury Fizycznej, Zdrowia i Turystyki, Uniwersytet Kazimierza Wielkiego w Bydgoszczy;   Streszczenie   Zespół przetrenowania (Overtraining syndrome - OTS) spowodowany jest zbyt dużymi obciążeniami oraz zaburzeniem równowagi i odpowiednich stosunków pomiędzy treningiem, a regeneracją. Zespół przetrenowania stanowi poważny problem we współczesnym sporcie, ponieważ może powodować nie tylko obniżenie lub całościową utratę formy zawodnika, ale również ma negatywny wpływ na jego zdrowie. W pracy zaprezentowano zjawisko zespołu przetrenowania. Opisano hipotezy dotyczące mechanizmu powstawania zespołu przetrenowania, jego przyczyny oraz objawy.   Abstract   Overtraining syndrome (OTS) is caused by too high loads and imbalance between training and recovery. It is a serious problem in modern sport, because it can cause not only an overall reduction or loss of form player, but also has a negative impact on the health of the player. The paper presents the phenomenon of overtraining syndrome. The paper describes the causes, symptoms and hypotheses about the mechanism of the overtraining syndrome.   Słowa kluczowe: zespół przetrenowania, medycyna sportowa.   Keywords: overtraining syndrome, sports medicine.